Firefly Cove - Bunn, T. Davis, 1952- (Bunn, T. Davis, 1952- Miramar Bay, 2018)
Since the age of seven, Lucius Quarterfield has known he is dying. But now, at twenty-eight, his time is finally running out. So he's returning to the one place he ever felt happy, near the only woman he ever truly wanted. He's going to make each moment count because he knows that everything is about to change...he just can't know exactly how.